“A Journey to Bilingualism” A Case Study of German-Turkish Bilingual Family - Serife Kalayci (Educational Process: International Journal)
The current study aims to investigate how a bilingual family perceives their bilingualism process and what they have done based on their attitudes and beliefs to support their children’s bilingual development. To that end, a family consisting of a German father, Turkish mother, 13-year old daughter, 9-year old son was asked to respond to interview questions. The results of the study showed that family used one person-one language strategy (Romaine, 1999) for raising bilingual kids. The father took the responsibility of raising the children bilingually and read books in the target language as an extra activity apart from always communicating in German with them. All of the participants seem to be aware of their weaknesses and strengths in their language competence.